BIOEKOLOGI VEKTOR MALARIA PADA BERBAGAI EKOSISTEM DI KABUPATEN DONGGALA, PROVINSI SULAWESI TENGAH - Riyani Setiyaningsih; Lasmiati Lasmiati; Mujiyono Mujiyono; Mega Tyas Prihatin; Heru Priyanto; Moulanda Maksud; Yuyun Srikandi; Risti Risti; Ika Martiningsih; Widiarti Widiarti; Triwibowo Ambar Garjito (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
Central Sulawesi is one of the malaria-endemic areas in Indonesia. Anopheles nigerrimus, Anopheles barbirostris, Anopheles subpictus, Anopheles parangensis, Anopheles flavirostris and Anopheles minimus were confirmed as malaria vectors. Researchers believed that there might have a distinctly different distribution and diversity of the vectors in different ecosystems. The purpose of the current study was to investigate and analyze the distribution and diversity of suspected malaria vectors (Anopheles spp.) in various ecosystems. Adult mosquitoes were collected using some methods e.g. human man landing method, animal baited trap, mosquito caught around the cage, using sweep net and the light trap. The sporozoites of Plasmodium infecting the caught mosquitoes were identified and examined using PCR. In addition, a survey on potential breeding sites of the mosquitoes. Based on the survey results, the mosquitoes species caught in the non-forest ecosystems near the settlements and positively infected by Plasmodium were An. ludlowae, An. flavirostris, and An. vagus. Meanwhile, the malaria vectors caught in the non-forest ecosystems far from the settlements were An. maculatus and An. subpictus. The results also demonstrated that An. barbirostris was detected as a malaria vector in the coastal area near the settlement. The ponds, rivers and fish farms were potential breeding sites for the mosquitoes. The suspected malaria vectors (Anopheles spp) spread throughout ecosystems e.g. forests, non-forests and coasts. The high risk of ecosystems for malaria transmission was the non-forest ecosystems near the settlements, the non-forest far away from the settlements, and the coasts near the settlements.